The Semi-Difference Entire Sequence Space 𝑐𝑠∩𝑑1 - N. Subramanian; K. Chandrasekhara Rao; K. Balasubramanian (International Journal of Mathematics and Mathematical Sciences)
Let Γ denote the space of all entire sequences. Let Λ denote the space of all analytic sequences. In this paper, we introduce a new class of sequence space, namely, the semi-difference entire sequence space 𝑐𝑠∩𝑑1. It is shown that the intersection of all semi-difference entire sequence spaces 𝑐𝑠∩𝑑1 is 𝐼⊂𝑐𝑠∩𝑑1 and Γ(Δ)⊂𝐼.